1998
DOI: 10.1038/sj.bmt.1701478
|View full text |Cite
|
Sign up to set email alerts
|

IFN-γ-mediated prevention of graft-versus-host disease: pharmacodynamic studies and influence on proliferative capacity of chimeric spleen cells

Abstract: Summary:Recently we demonstrated that prolonged administration of IFN-␥ prevented the development of GVHD in a MHC-mismatched murine BMT model. Treatment with IFN-␥ allowed the development of mature donorderived allo-tolerant immunocompetent cells in complete chimeric recipients. Here we present data on the pharmacodynamics of this cytokine-mediated protection against GVHD. Treatment with 50 000 U IFN-␥ twice weekly for a period of 5 weeks, starting at the day of BMT, was shown to be the optimal treatment prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 14 publications
(20 reference statements)
1
22
0
1
Order By: Relevance
“…In contrast, early administration has a protective effect. 38 Yang et al 39 have demonstrated that IL-12 injected at the same time as the BM transplant protected animals from GVHD and that this protection is dependent on the ability of the donor cells to produce IFN-␥. Similarly, in our studies the high levels of IFN-␥ produced by the expanded CD8 ϩ NKT cells appears to protect animals from otherwise lethal GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, early administration has a protective effect. 38 Yang et al 39 have demonstrated that IL-12 injected at the same time as the BM transplant protected animals from GVHD and that this protection is dependent on the ability of the donor cells to produce IFN-␥. Similarly, in our studies the high levels of IFN-␥ produced by the expanded CD8 ϩ NKT cells appears to protect animals from otherwise lethal GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Possession of allele 3 in the recipient genotype in HLA-matched sibling transplants was associated with development of acute GvHD. It has therefore been suggested that IFNc may be involved in the down-regulation of GvHD via a negative feed-back loop (Brok et al 1998).…”
Section: Ifncmentioning
confidence: 99%
“…now been associated with GvHD and HSCT transplant outcomes (Brok et al, 1998;Fishman et al, 1998;Middleton et al, 1998;Cavet et al, 1999Cavet et al, , 2001Grainger et al, 1999;Cullup et al, 2001Cullup et al, , 2003Socié et al, 2001;Hattori et al, 2002;Ishikawa et al, 2002;Kögler et al, 2002;Rocha et al, 2002;Lin et al, 2003;MacMillan et al, 2003a;Stark et al, 2003;Keen et al, 2004).…”
Section: Il-10mentioning
confidence: 99%
“…В опытах на мышах показано, что время отторжения аллогенных ор-ганов значительно пролонгируется в условиях повышенной активности IDO, в частности с по-мощью одновременной трансплантации органа и ДК донора, продуцирующих IDO, или с помо-щью IFNγ, введенного сразу же после трансплан-тации клеток костного мозга. В последнем случае тормозилось развитие РТПХ [10].…”
Section: козлов ва демина дв Medical Immunology (Russia)/meditsiunclassified